Preliminary study of the interaction between kejawen esoteric and wild macaques in kalisalak forest, central java-indonesia - Al-Hakim, Rosyid; Hidayah, Hexa; Putri, Esa R. C.; Karsam, Karsam (Lembaga Layanan Pendidikan Tinggi Wilayah I Sumatra Utara (LLDikti I), 2024)
Ethnobiology became a research trend of human-integrated biology-ethnicity to support their lives. Ethnobiology for ethnic and indigenous peoples continued to be passed down by belief in each generation—Indigenous peoples in Central Java-Indonesia, Kejawen esoteric, whose lives always coincide with ethnobiological science. A previous study reported the preliminary study of the interaction between Kejawen esoteric and wild macaques at Kalisalak Forest, Central Java-Indonesia, but it is unclear. This study is an extended version of the previous study that explains more about the human-primate interaction at Kalisalak Forest. The method used in-depth interviews with 83 householders that believed in Kejawen's esoteric faith. Ethnobiological studies discussed are in the form of ethnobotany and ethnozoology (ethnoprimatology). This study result shows that there is no visible relationship between Kejawen esotericism and the presence of wild macaques in the Kalisalak forest, as well as indigenous Kejawen esoteric really cares about the wild macaque’s population in other ways—the interaction related to supporting the biodiversity and SDGs 2030's goals.